Animal facility videoendoscopic intubation station: tips and tricks from mice to rabbits. (April 2017) - Miranda, Alice; Pêgo, José M; Correia-Pinto, Jorge
Endotracheal intubation of laboratory animals is a common procedure shared by several research fields for different purposes, such as mechanical ventilation of anaesthetized animals, instillation of cytotoxic nanoparticles, infectious agents or tumour cells for induction of disease models, and even for diagnostic and therapeutic purposes. These different research purposes, achieved in different animal models, require technical expertise and equipment that suits every research need from animal facilities. In this short report we propose a videoendoscopic intubation station that could be shared among the most common laboratory animals, namely the mouse, rat, guinea pig and rabbit, from neonates to adult animals. This report aims to contribute to the reduction of animals excluded from experiments due to false paths during direct and blind intubations and to the refinement of procedures by replacing surgical approaches such as tracheotomy.